Study of hydraulic conductivity and pollutant transport parameters in a municipal solid waste disposal area - Yacoub, Jhaber Dahsan [UNESP] (2024)
Municipal solid waste (MSW) disposal sites play a vital role in waste management but pose significant environmental risks due to the transport of contaminants into soil and groundwater. This work examines these risks through an integrative study comprising experimental, analytical, and numerical analyses. A detailed experimental investigation of the tropical soil profile and weathered sandstone near Brazil's Bauru MSW disposal site revealed key geotechnical and hydraulic properties influencing contaminant transport, including anisotropic permeability and expansive behaviors attributed to clay minerals. Laboratory column tests using the non-reactive tracer NaCl and heavy metals (Mn, Ni, Pb) identified hydraulic conductivity (k), dispersivity (α), hydrodynamic dispersion (Dh), retardation factor (Rd), and partition coefficient (Kd) as critical parameters. Numerical simulations using CODE_BRIGHT evaluated the fate and transport of contaminants in Bauru's MSW disposal site's North-South and East-West profiles over 1, 10, and 100 years under varying leachate heads. Results show that increased leachate head accelerates breakthrough times, with horizontal flow dominating permeable soil horizons. The East-West profile exhibited greater vulnerability to contaminant migration, though sandstone layers provided some attenuation. These findings underscore the importance of integrating field data, laboratory experiments, and modeling to enhance MSW disposal site management strategies, mitigate contamination risks, and safeguard environmental resources.